Situation Report: Romania, 17 December 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Jaruzelski's Lightning Visit to Romania / by Anneli Maier Foreign Minister Replaced, Appointed CC Secretary / by Anneli Maier Ceausescu Rejects Reform, Enforces Austerity Course / by Anneli Maier Elena Ceausescu Marches on and Up / by Anneli Maier The Electricity Crisis / by Paul Gafton Army Officers Powerless in Energy Crisis / by Slobodan Stankovic Inspection Teams at Work / by Dan Ionescu More Problems in the Food Supply / by Paul Gafton Nationalizing Food Consumption / by Dan Ionescu AIDS as an Instrument of Anti-Western Propaganda / by Carmen Pompey